The treasure hunters club : a mystery - Ryan, Tom, 1977 February 26- (Atlantic Monthly Press, 2024)
"Welcome to Maple Bay, Nova Scotia. For nearly a century, people have ventured to the idyllic seaside town of Maple Bay in search of a legendary lost pirate treasure, but locals know there's more than just gold buried in the sand. As the paths of three strangers converge in Maple Bay, the truth is about to be blown wide open. But not before the bodies start to pile up. Peter Barnett is rapidly approaching forty with little to show for it when a mysterious letter invites him to Maple Bay and the mansion his estranged family has called home for generations. Seventeen-year-old Dandy Feltzen is isolated and adrift following the death of her beloved grandfather, until his final request and a tantalizing clue sets her on a mission to solve the mystery he spent his entire life chasing. Cass Jones has given up on her dream of being a successful author when an unexpected opportunity lands in her lap: a housesitting gig in remote Maple Bay, where she stumbles on the perfect subject matter for her breakout book -- and the handsome sailor who might be just the person to help her research it. Peter, Dandy, and Cass have never met, but they're on a collision course with each other and the mystery that has defined Maple Bay for two centuries, and none of them are prepared for the shocking truths that may or may not still be buried there."--